Comprehensive evaluation of Korla fragrant pears and optimization of plucking time during the harvest period - Wang, Zhentao; Tang, Yurong; Jin, Xiaozhen; Liu, Yang; Zhang, Hong; Niu, Hao; Lan, Haipeng (International Journal of Agricultural and Biological Engineering, 2022)
To optimize the harvest of Korla fragrant pears and to provide a theoretical basis for post-harvest processing, a total of 26 basic indices of Korla fragrant pears, including their morphology, quality, and softening age, were investigated. The harvest period ranged from August 22nd to October 6th, samples were collected every 5 d (totally 10 plucking days, indicated as H1-H10). The results indicated that changes in pectin content were the main causes of softening in fragrant pears. The scavenging of free radicals mainly occurred because of the collaborative effects of superoxide dismutase (SOD) and catalase (CAT). In the harvest periods H1-H3, the hardness, titratable acid (TA), chlorophyll content, density, and diameter of the stone cells, as well as the cellulose and hemicellulose content of the Korla fragrant pears were at their highest. During the periods H7-H10, the single-fruit weight, fruit horizontal and vertical diameter, color coordinates L, a*, b*, soluble-solids content (SSC), SOD activity, CAT activity, and water-soluble pectin were higher than in the other plucking periods. The highest vitamin C (VC) content and moderate values for a variety of indicators were observed during H3-H7. Variations in the Korla fragrant pears during H1-H3 mainly manifested through changes in softening-related parameters. During H3-H10, changes in the softening-related, aging-related, color-related, and quality indices had a dominant role. On this basis, some suggestions for the post-harvest processing of fragrant pears have been proposed. Fruit, during H1-H3, are suitable for transportation and storage; during H7-H10 are suitable for fresh-eating and further processing; and during H3-H7, exhibited moderate values for a variety of indicators and had the highest commercial value. This research provides a systematic evaluation of the characteristics of mature Korla fragrant pears during the harvest period and can form the basis for fruit quality control and processing of Korla fragrant pears.Keywords: Korla fragrant pear, harvest period, plucking time, quality, fruit maturity, evaluation, optimizationDOI: 10.25165/j.ijabe.20221503.6474Citation: Wang Z T, Tang Y R, Jin X Z, Liu Y, Zhang H, Niu H, et al. Comprehensive evaluation of Korla fragrant pears and optimization of plucking time during the harvest period. Int J Agric & Biol Eng, 2022; 15(3): 242–250.